"Каштанка" и другие рассказы - Чехов Антон Павлович (Школьная библиотека, 2013)
Экземпляры: ДБаб (20240523) / Инвентарный номер: 57422 / Цена: 90.00 / Авт.знак: Ч-56 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1